2023
DOI: 10.1039/d3cp00156c
|View full text |Cite
|
Sign up to set email alerts
|

2D noble metals: growth peculiarities and prospects for hydrogen evolution reaction catalysis

Abstract: High-performance electrocatalysts for hydrogen evolution reaction are of interest in the development of next-generation sustainable hydrogen production systems. Although expensive platinum-group metals have been recognized as the most effective HER...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 117 publications
0
1
0
Order By: Relevance
“…The search for high-performance and low-cost electrocatalysts is the key to replace fossil fuels by electrocatalytic energy conversion technology to diminish the increasing energy consumption and environmental crisis. Fuel cells, metal-air batteries, and electrochemical fuel productions are the representatives of pivotal renewable energy technologies [1][2][3][4][5][6]. Nonetheless, the primary electrode reactions in fuel cells * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search for high-performance and low-cost electrocatalysts is the key to replace fossil fuels by electrocatalytic energy conversion technology to diminish the increasing energy consumption and environmental crisis. Fuel cells, metal-air batteries, and electrochemical fuel productions are the representatives of pivotal renewable energy technologies [1][2][3][4][5][6]. Nonetheless, the primary electrode reactions in fuel cells * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Regrettably, the process of the reaction intermediate desorbing from catalyst surfaces to create the end product is challenging without electrocatalyst assistance, owing to significant thermodynamic and kinetic reaction hindrances, along with the inappropriate adsorption and desorption abilities of the reaction intermediates (H * and O * ) [9][10][11][12]. Noble metal catalysts (NMCs) can reduce the activation barriers and promote the above-mentioned reaction process due to their electronic structure effect and surface structure effect [5,[13][14][15][16][17]. In the ORR, a significant positive potential can be generated by the four-electron process and thus Pt-based electrocatalysts become the benchmark electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In attempts to replace platinum-based electrocatalysts with precious-metal-free electrocatalysts for the HER, numerous non-noble compounds, such as transition metal oxides, sulfides, phosphides, nitrides and carbides, have been explored to achieve the required catalytic activity for industrial purposes. 8–11 Cobalt and its compounds have attracted particular attention due to their low cost and favorable conductivity with high catalytic efficiency. 12,13 For example, Xue et al 14 reported that Co/CoP nanoparticles could achieve a current density of 10 mA cm −2 in neutral electrolyte at 1.51 V. In energy conversion and storage devices, coating or directly growing active electrode materials on the necessary conductive substrates are effective strategies for enhancing the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, a coating is recognized as the most feasible, cost-efficient, and efficient approach toward increasing corrosion resistance, divided by two main non-metallic and metal-based techniques [6,7]. For example, the epoxy coating prepared by Tong Liu et al has efficient self-healing performance [8].…”
Section: Introductionmentioning
confidence: 99%